Gender-based violence and unwanted sexual behaviour in Canada, 2018: Initial findings from the Survey of Safety in Public and Private Spaces - Cotter, Adam; Savage, Laura (Juristat, 2019)
Women were also more likely to have talked to somebody about their experience following an incident of unwanted behaviour or assault. * Women were more likely than men to have experienced multiple incidents in the past 12 months and to have experienced unwanted behaviour or violence while on the street versus while in another public place, such as a bar or restaurant. * Beside gender, being younger, having experienced harsh parenting, having been physically or sexually abused by an adult during childhood, and being single, never married, all play a role in experiencing gender-based violence. * One in three (32%) women and one in eight (13%) men experienced unwanted sexual behaviour in public. The victims-and even the perpetrators-may not themselves perceive the motivations for the incident as being rooted in social structures and systems, which can serve to produce and reproduce gender inequality and gendered violence across many dimensions. Because of this, asking about gender-based violence directly in a survey may not lead to accurate findings or conclusions. Previous research indicates that disabled women, Indigenous women, girls and young women, lesbian and bisexual women, and gay and bisexual men are more at risk of experiencing violence (Boyce 2016; Burczycka 2018a; Conroy 2018; Conroy and Cotter 2017; Cotter 2018; Cotter and Beaupré 2014; Ibrahim 2018; Perreault 2015; Rotenberg 2019; Rotenberg 2017; Simpson 2018). By also including questions which measure violence that meets the criminal threshold, such as physical and sexual assault, the SSPPS allows for a comparative analysis of the risk factors across the continuum of gender-based violence, while also providing more recent self-reported statistics on violent victimization.
Place: Ottawa